2010
DOI: 10.1007/s00018-010-0507-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a bacterial inhibitor against g-type lysozyme

Abstract: Lysozymes are antibacterial effectors of the innate immune system in animals that hydrolyze peptidoglycan. Bacteria have evolved protective mechanisms that contribute to lysozyme tolerance such as the production of lysozyme inhibitors, but only inhibitors of chicken (c-) and invertebrate (i-) type lysozyme have been identified. We here report the discovery of a novel Escherichia coli inhibitor specific for goose (g-) type lysozymes, which we designate PliG (periplasmic lysozyme inhibitor of g-type lysozyme). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 47 publications
2
48
0
Order By: Relevance
“…In documented studies of recombinant lysozyme inhibitors, the recombinant proteins were used at the dose of 10 M to 200 M for different analyses (13,17); in our study, the concentration of rMliC used (80 M) relatively high based on the consideration that the protein had undergone reconstitution. Previous studies showed that in the presence of outer membrane permeabilizers or antimicrobials that destabilize the outer membrane of Gram-negative bacteria, lysozymes can effectively kill Gram-negative bacteria (14,16,17,(33)(34)(35). In our study, we found that in the presence of diluted fish serum, which facilitates the action of lysozymes on Gram-negative bacteria, rMliC reduced the killing effect of HEWL The fish were monitored daily for mortality and survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In documented studies of recombinant lysozyme inhibitors, the recombinant proteins were used at the dose of 10 M to 200 M for different analyses (13,17); in our study, the concentration of rMliC used (80 M) relatively high based on the consideration that the protein had undergone reconstitution. Previous studies showed that in the presence of outer membrane permeabilizers or antimicrobials that destabilize the outer membrane of Gram-negative bacteria, lysozymes can effectively kill Gram-negative bacteria (14,16,17,(33)(34)(35). In our study, we found that in the presence of diluted fish serum, which facilitates the action of lysozymes on Gram-negative bacteria, rMliC reduced the killing effect of HEWL The fish were monitored daily for mortality and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Lysozyme-inhibitory activity of rMliC. Since lysozyme inhibitors in their natural forms are usually difficult to obtain, especially with relatively high purity, these proteins have been studied in the form of recombinant proteins (13,17,20,21,32). In our study, to examine the biological activity of MliC Et , rMliC was purified from E. coli as a Trx-tagged protein.…”
Section: Sequence Of Mlic Etmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, knockout of ivy, the gene encoding one of the inhibitors of c-type lysozyme, slightly reduced the survival of Escherichia coli in chicken egg albumen, thus demonstrating a possible ecological significance for this inhibitor (7). Interestingly, we found recently that E. coli and some other Gram-negative bacteria like Salmonella also produce a g-typespecific lysozyme inhibitor (PliG) (22). Since these bacteria closely interact with vertebrate hosts, which can produce both c-and g-type lysozymes, the cooccurrence of c-and g-type inhibitors supports the hypothesis that they are involved in the host interaction of these bacteria.…”
mentioning
confidence: 94%
“…Over the last 10 years, specific inhibitors of c-, g-, and i-type lysozymes have been discovered in Gram-negative bacteria (1,15,23,22) and in vitro experiments have shown that they protect the bacteria against the corresponding lysozymes when the outer membrane is permeated by lactoferrin or EDTA (1,6,23,22). In addition, knockout of ivy, the gene encoding one of the inhibitors of c-type lysozyme, slightly reduced the survival of Escherichia coli in chicken egg albumen, thus demonstrating a possible ecological significance for this inhibitor (7).…”
mentioning
confidence: 99%